Promoting labour market integration of refugees with trade preferences: Beyond the EU-Jordan compact - Heliodoro Temprano Arroyo (Kiel Institute for the World Economy (IfW), 2018)
Trade preferences provide a potential policy tool for supporting refugee employment in countries of first asylum. Thus, in the context of the EU-Jordan Compact agreed in 2016, the EU eased the rules of origin for Jordanian exporters employing a minimum share of Syrian refugees. The use of trade preferences to encourage the labour market integration of refugees is consistent with the new, developmental approach to refugee protection advocated by the recent literature and enshrined in the Comprehensive Refugee Response Framework adopted by the UN in 2016. The paper looks at the so-far disappointing impact of the EU-Jordan agreement on rules of origin, as well as the experience with two relevant U.S. preferential programmes (the Qualified Industrial Zones initiative for Egypt and Jordan and the African Growth and Opportunity Act) that have generated substantial export growth and employment. It then discusses the conditions under which trade preferences can prove an effective instrument for refugee integration and makes some concrete policy recommendations.
Keywords: F13; F22; 330; migration; refugees; integration; trade preferences